Loyalitas Nasabah Pada Bank Syariah Indonesia: Peran Kualitas Pelayanan, Atribut Produk Islami, dan Citra Perusahaan - Pasya, Andhira Juanita; Widyaningsih, Meilana (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the effect of service quality, Islamic product attributes, and corporate image on customer loyalty with the aim of continuous improvement and customer balance at Bank Syariah Indonesia (BSI). The data type used in the study is quantitative, with primary data. The population used in this research were all Bank Syariah Indonesia customers in Surakarta. They were collected using questionnaires physically and online to Bank Syariah Indonesia (BSI) customers. The questionnaires collected were 138 respondents to be used as samples and then analyzed using SPSS 23. The analysis method used was multiple linear regression analysis. The research results showed: that (1) service quality has no effect on customer loyalty, (2) Islamic product attributes have an effect on customer loyalty, and (3) company image has an effect on customer loyalty.